Economic Considerations for Advancement Through the Progressive Control Pathway: Cost–Benefit Analysis of an FMD Disease-Free Zone in Punjab Province, Pakistan - Lyons, Nicholas A.; Afzal, Muhammed; Toirov, Farrukh; Irshad, Aamer; Bartels, Chris J. M.; Rushton, Jonathan (Frontiers in Veterinary Science, 2021)
Foot-and-mouth disease (FMD) is a priority disease of livestock in Pakistan, which was classified in stage 2 of the Progressive Control Pathway (PCP-FMD) in 2015, aiming to reduce disease impact. Further progression requires efforts to reduce viral circulation that may ultimately result in being awarded official disease-free status by the World Organisation for Animal Health [Office International des Epizooties (OIE)]. Typically, FMD control is reliant on the extensive use of vaccines, requiring careful consideration of the costs and benefits to ensure investment is likely to provide a positive return. This study conducted a cost–benefit analysis (CBA) for a proposed zone within Punjab Province, Pakistan. Benefits were assumed to come from averted production losses and treatment costs and the costs based on typical measures required for establishing a disease-free zone. To estimate the impact of FMD at the farm level, models were created to estimate effects on milk production, offtakes, and changes in herd value over a 5-year period with different parameters used to represent the production systems present. Control strategy costs incorporated aspects of vaccination, surveillance, sanitary measures, program management, stakeholder engagement, preparatory studies, training, and capacity building. The results indicated a median benefit–cost ratio of 1.03 (90% central range 0.37, 1.63) with a median net present value of 1.99 billion Pakistan Rupees (90% central range −37.7, 37.0). The greatest cost was due to vaccination at 56%, followed by sanitary measures (including implementing and maintaining an animal ID system and quarantine stations around the zone) at 41%. Although the median benefit–cost ratio and net present value indicated that investment is likely to generate a positive return, the large variation indicates caution in interpreting the results and it is possible that an increase in animal value through new export markets will be required. Further refinement in our knowledge of disease impact and the details of the control strategy are needed. Moreover, there are implications regarding vaccine security, since the strategy is reliant on the steady provision of quality vaccines in order to achieve the anticipated benefits, raising important issues on vaccine availability for countries to maintain lucrative export markets for FMD.